INDIKASI PERMUKIMAN SITUS-SITUS BERCIRI AUSTRONESIA DI PANTAI TIMUR DAN SELATAN PULAU SELAYAR - nfn Hasanuddin (WalennaE, 2009)
The arrival of Austronesian communities in South and Southeast Sulawesi did not occur at the same time. Allegedly the coast of South and Southeast Sulawesi mainland inhabited earlier than the small islands to the south. The strategy used is a survey primarily on sites along the east coast and southern Selayar Island. The entire site is the coast with a discovery of a corpse coffin was left of human bones are stored in a cave, bronze bracelets, and artifacts of stone tools and fragments of pottery. Utilization of caves and niches shows a multi-residential space that functions as a dwelling (with indication of shellfish), industrial (with indication of stone tools and chips/waste rock), and the burial place (which proved the discovery of human bones and container tomb called duni placed in the cave).Kedatangan masyarakat Austronesia di Sulawesi Selatan dan Tenggara tidak terjadi pada saat yang bersamaan. Diduga pantai daratan Sulawesi Selatan dan Tenggara dihuni lebih awal dari pulau-pulau kecil di selatan. Strategi yang digunakan adalah survei terutama pada situs di sepanjang pantai timur dan Pulau Selayar selatan. Seluruh situs adalah pantai dengan penemuan peti kubur yang tersisa dari tulang manusia yang disimpan di gua, gelang perunggu, dan artefak alat-alat batu dan pecahan tembikar. Pemanfaatan gua dan ceruk menunjukkan ruang multi-residen yang berfungsi sebagai tempat tinggal (dengan indikasi kerang), industri (dengan indikasi alat-alat batu dan keripik / batuan sisa), dan tempat pemakaman (yang membuktikan adanya penemuan tulang manusia dan wadah makam yang disebut duni ditempatkan di gua).